The technique of making Super - realism sculptures by Local alternative materials (Applied Study) (Al-Academy, 2016)
This research is studying technique sculptures super - realism, search through, how the method of work, and the search for the materials used in their manufacture, and this is the first study in the field of art and the field of academic study in the country.Research consists of an introduction, And four sections, The introduction containing information on: research problem, Importance of research, Goals of the research, Limits of research, research approach, and research tools.The first section contains a technical study sculptures super -realism in contemporary sculpture, while the second section includes a search for alternative materials available in the local markets, for making sculptures super - realism, the third section dedicated for testing, and the fourth section contains the results of the search. And it was the most important results:1.Research experiments proved successful in the use of alternative materials, for making sculptures, and can be obtained from local markets.2.Industry sculptures super - realism, depend on the regular way, and also, depends on the a great experience sculptor , in: anatomy, techniques material